Insular Christianity : alternative models of the Church in Britain and Ireland, c.1570-c.1700 - Armstrong, Robert (Robert Matthew); Ó hAnnracháin, Tadhg (Politics, culture, and society in early modern Britain., 2013)
This focused collection of essays on the alternative establishments which both Presbyterians and Catholics attempted to create in Britain and Ireland offers a dynamic new perspective on the evolution of post-reformation religious communities within Britain and Ireland.